High levels of a comprehensive set of matrix metalloproteinases in endometriotic lesions: validating the key role of cellular senescence in endometriosis pathogenesis - Laura Palmieri; Helena Malvezzi; Bruna Cestari de Azevedo; Eduardo Varejão Díaz Placencia; Eliane Antonioli; Sérgio Podgaec (Einstein (São Paulo))
ABSTRACT Objective: To investigate the roles of cellular senescence and dysfunctional extracellular matrix metalloproteinases (MMPs) in perpetuating chronic inflammation and facilitating the establishment of endometriotic lesions. By analyzing the MMP activity in the endometrial tissue and peritoneal fluid, we aimed to obtain novel insights into the molecular mechanisms underlying endometriosis-related pathophysiology. Methods: The endometrial tissue and peritoneal fluid samples were collected laparoscopically from 12 women with endometriosis and 16 healthy controls. Gelatin zymography was performed to assess the activity of MMP-2, and multiplex assays were performed to determine the concentrations of MMP-1 and MMP-3 proteins. Statistical analyses were performed using Generalized Linear Models (GzLM) and SPSS software. Results: Gelatin zymography revealed higher pro-MMP-2 activity in endometriotic lesions than in eutopic and control endometrium. However, no differences were observed in peritoneal fluid samples. Additionally, MMP-1 and MMP-3 protein levels were elevated in endometriotic lesions compared with those in the eutopic endometrium, whereas only MMP-3 was increased compared with that in the control. No statistical significance was observed for MMP-2, MMP-1, and MMP-3 in the peritoneal fluid samples. Conclusion: Increased levels of MMP-1, MMP-2, and MMP-3 in endometriotic lesions indicate that endometriosis may have a unique metabolomic signature linked to cell cycle arrest and inflammation. This may contribute to the pathogenesis of endometriosis by facilitating implantation of ectopic endometrium-like tissue in a disturbed immune environment.